Analyzing the link between built environment and physical activity: a spatial study in suburban area - Iamtrakul, Pawinee; Chayphong, Sararad (Frontiers in Built Environment, 2024)
Promoting physical activity is a significant concern that contributes to urban development, thereby fostering good health among city residents. This imperative highlights the interconnectedness between public health initiatives and the advancement of urban landscapes, reflecting the interdisciplinary nature of environmental science. Hence, this study aims to investigate the correlation between the built environment and access to physical activities within distinct local contexts. Utilizing the ordinary least squares estimation technique alongside spatial statistical analysis tools can facilitate the exploration of spatial disparities and interdependencies. Results pertaining to the built environment indicate significant differences within the built group context at a p-value level of 0.000. This suggests that within the local context, various activities, including those related to the transportation system, differ throughout the city. Findings regarding the link between the built environment and physical activity indicate that the relatively low R-squared values (0.10 -0.20) may be attributed to the presence of grid areas with minimal walking distances. This finding underlines the key role of the built environment in promoting physical activity, highlighting the importance for urban planning and design to prioritize enhancements in active transportation infrastructure and increase access to urban activity nodes. This can be achieved by strategically distributing physical activity opportunities and ensuring accessibility via active transportation and public transit.